Intra‐operative fluorescence‐based detection of positive surgical margins during radical prostatectomy: Lessons learned from a pilot ex vivo translational study. Issue 2 (27th December 2022) - Fiard, Gaelle; Hughes, Cecilia; Heus, Redha; Abert, Bruno; Chipon, Emilie; Boudry, Isabelle; Saada‐Sebag, Geraldine; Kassem, Maysoun; Lanchon, Cecilia; Long, Jean‐Alexandre; Descotes, Jean‐Luc; Moreau‐Gaudry, Alexandre; et al.
Abstract: Objectives: Nerve‐sparing techniques during radical prostatectomy have been associated with an increased risk of positive surgical margins. The intra‐operative detection of residual prostatic tissue could help mitigate this risk. The objectives of the present study were to assess the feasibility of using an anti‐prostate‐specific membrane antigen (anti‐PSMA) antibody conjugated with a fluorophore to characterize fresh prostate tissue as prostatic or non‐prostatic for intra‐operative surgical margin detection. Methods: Fresh prostatic tissue samples were collected from transurethral resections of the prostate (TURP) or prostate biopsies, and either immunolabelled with anti‐PSMA antibody conjugated with Alexa Fluor 488 or used as controls. A dedicated, laparoscopy‐compliant fluorescence device was developed for real‐time fluorescence detection. Confocal microscopy was used as the gold standard for comparison. Spectral unmixing was used to distinguish specific, Alexa Fluor 488 fluorescence from nonspecific autofluorescence. Results: The average peak wavelength of the immuno‐labeled TURP samples ( n = 4) was 541.7 ± 0.9 nm and of the control samples ( n = 4) was 540.8 ± 2.2 nm. Spectral unmixing revealed that these similar measures were explained by significant autofluorescence, linked to electrocautery. Three biopsy samples were then obtained from seven patients and also displayed significant nonspecific fluorescence, raising questions regarding the reproducibility of the fixation of the anti‐PSMA antibodies on the samples. Comparing the fluorescence results with final pathology proved challenging due to the small sample size and tissue alterations. Conclusions: This study showed similar fluorescence of immuno‐labeled prostate tissue samples and controls, failing to demonstrate the feasibility of intra‐operative margin detection using PSMA immuno‐labeling, due to marked tissue autofluorescence. We successfully developed a fluorescence device that could be used intraoperatively in a laparoscopic setting. Use of the infrared range as well as newly available antibodies could prove interesting options for future research.